Предмет: Алгебра,
автор: Baekhyuneee0461
Помогите сделать шестое, пожалуйста ~
Приложения:
Ответы
Автор ответа:
0
ОЗ (x-1)(x²+x+1)≠0 x²+x+1>0 при любом х,т.к.D<0⇒x-1≠0⇒x≠1
(x+36)+(x-6)(x²+x+1)-(x²-x+16)(x-1)=0
x+36+x³+x²+x-6x²-6x-6-x³+x²-16x+x²-x+16=0
-3x²-21x+46=0
3x²+21x-46=0
D=441+552=993
x1=(-21-√993)/6
x2=(-21+√993)/6
(x+36)+(x-6)(x²+x+1)-(x²-x+16)(x-1)=0
x+36+x³+x²+x-6x²-6x-6-x³+x²-16x+x²-x+16=0
-3x²-21x+46=0
3x²+21x-46=0
D=441+552=993
x1=(-21-√993)/6
x2=(-21+√993)/6
Похожие вопросы
Предмет: Физика,
автор: sar1k1azi
Предмет: Алгебра,
автор: berenov67
Предмет: Физика,
автор: anastasiapustovit933
Предмет: География,
автор: имишка
Предмет: Математика,
автор: костяб1151456547